Successful Treatment of Advanced Primary Cutaneous Apocrine Carcinoma on the Scrotum with Systemic Chemotherapy and Radiotherapy Followed by Denosumab - Furudate, Sadanori (Case Rep Oncol, 2017)
Primary cutaneous apocrine carcinoma (PCAC) is a rare and highly aggressive cutaneous adnexal type of tumor that has a high metastasis rate and a poor prognosis. Although there are several case reports describing the successful treatment of PCAC with chemoradiotherapy or molecular targeting therapy, no standard therapy for the treatment of advanced PCAC has been established yet. Since receptor activator of nuclear factor kappa-B ligand (RANKL) is expressed in cancers of apocrine origin, leading to immunosuppression at the tumor site, we hypothesized that targeting RANKL with denosumab might be useful for the treatment of PCAC. In this report, we describe a case with advanced PCAC on the scrotum successfully treated with systemic chemotherapy using carboplatin and paclitaxel, and radiotherapy followed by denosumab.